Paradoxical deterioration in seizure control due to anticonvulsant-induced hypocalcaemia. Issue 12 (5th December 2019) - Gauci, Zachary; Rizzo, Christopher; Mifsud, Simon; Cachia, Mario J
Abstract : Hepatic cytochrome P450 enzyme induction is associated with certain antiepileptic drugs (AEDs) and may result in hypocalcaemia secondary to vitamin D deficiency. We report a case of a 44-year-old man with a history of epilepsy, who presented with breakthrough seizures after having previously been seizure-free for 11 years. Investigations revealed severe hypocalcaemia with a corrected calcium of 1.7 mmol/L. His phenytoin dose was increased, and he was started on calcium supplementation. He was discharged with a corrected calcium level of 2.05 mmol/L but was readmitted 1 week later with further seizures and a corrected calcium of 1.89 mmol/L. 25-hydroxyvitamin D was low. AED-induced hypocalcaemia was suspected, which had been made paradoxically worse by the increase in phenytoin dose. Alfacalcidol was prescribed and he was switched from phenytoin to levetiracetam with resolution of hypocalcaemia and no further seizures. The authors recommend screening for calcium and vitamin D deficiency in patients on enzyme-inducing AEDs.